2014
DOI: 10.1186/s13550-014-0059-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of retinol binding protein 4 and carbamoylated haemoglobin as potential renal toxicity biomarkers in adult mice treated with 177Lu-octreotate

Abstract: BackgroundThe kidneys are regarded as one of the main dose-limiting organs in the treatment of neuroendocrine tumours with 177Lu-[DOTA0, Tyr3]-octreotate (177Lu-octreotate), despite the successful use of kidney uptake blocking agents such as lysine and arginine. To avoid renal toxicity but still give each patient as high amount of 177Lu-octreotate as possible, there is a need for methods/biomarkers that indicate renal injury in an early stage of the treatment. The aim of this study was to investigate the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…The intermediate reaction has been suggested to be reversible in the literature (Rxn 2). 41 This fits the data from this study because an increased amount of ammonium in the system will shift this equilibrium toward urea decreasing the concentration of cyanate and thus decreasing the rate of Rxn 3. It has also been observed that CBZ will break down to form ISB in acetic acid without the presence of any other reagents, and so reaction (4) has been included in the network.…”
Section: Reverse Reaction Modelingsupporting
confidence: 87%
“…The intermediate reaction has been suggested to be reversible in the literature (Rxn 2). 41 This fits the data from this study because an increased amount of ammonium in the system will shift this equilibrium toward urea decreasing the concentration of cyanate and thus decreasing the rate of Rxn 3. It has also been observed that CBZ will break down to form ISB in acetic acid without the presence of any other reagents, and so reaction (4) has been included in the network.…”
Section: Reverse Reaction Modelingsupporting
confidence: 87%
“…It would clearly be of great benefit to determine a plasma parameter or marker in the urine, which would allow identification of renal injury at an early stage after radionuclide therapy. In this respect the retinol binding protein 4 may be a useful marker as recently demonstrated [30].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…In a population of type 2 diabetics with and without CKD, serum retinol binding protein was however not related to carotid intima thickness [ 498 ]. On the other hand urinary retinol binding protein was inversely related to kidney function and cardiovascular risk factors [ 499 ] and was also increased in proportion with the degree of renal radiation damage in mice [ 500 ].…”
Section: Middle Moleculesmentioning
confidence: 99%